Physical and morphological characteristics of edible coatings based on pectin and guava by-products applied to guava pieces - Todisco, Katieli Martins [UNESP]; Pérez-monterroza, Ezequiel José [UNESP]; Janzantti, Natália Soares [UNESP]; Mauro, Maria Aparecida [UNESP] (Universidade Federal de Santa Maria, 2021)
Edible coatings based on polysaccharides have been applied on pieces of fruits and vegetables before drying because of their potential to improve physical and nutritional characteristics of dehydrated plant foods. In the present study, physical and thermal properties of pectin-based films, with and without the incorporation of by-products obtained from the processing of red guava, were determined. These properties allow one to predict the likely behaviour of these films when used as edible coatings on guava pieces, during and after their dehydration. Thus the structural and morphological characteristics and the physical, thermal and sorption properties of the films and of the fruit pulp were determined, using scanning electronic microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD) and the static gravimetric method to determine the water-sorption curves. The addition of by-products provided crystallinity to the pectin film, attributed to their cellulose content, and hardly altered the water retention capacity of the pectin films. However, the pectin contributed to presenting a slightly higher sorption moisture at equilibrium, as compared to the guava pulp. The glass transition temperatures reported at extremely low moisture contents, both in the pulp and in the films with added by-products, indicated that at intermediate moisture contents, the fruit/film ensemble was in the rubbery state at room temperatures, providing softness to the dehydrated product. The images showed good integration of the edible films with the surface of the guava pieces.

Revestimentos comestíveis à base de polissacarídeos têm sido aplicados em pedaços de frutas e vegetais antes da secagem devido ao seu potencial de melhorar as características físicas e nutricionais de alimentos vegetais desidratados. No presente estudo, foram determinadas as propriedades físicas e térmicas de filmes à base de pectina, com e sem a incorporação de subprodutos obtidos do processamento da goiaba vermelha. Essas propriedades permitem prever o provável comportamento desses filmes quando usados ​​como cobertura comestível em pedaços de goiaba, durante e após a sua desidratação. Assim, foram determinadas as características estruturais e morfológicas e as propriedades físicas, térmicas e de sorção dos filmes e da polpa do fruto, utilizando microscopia eletrônica de varredura (MEV), calorimetria exploratória diferencial (DSC), difração de raios X (DRX) e método gravimétrico estático para determinação das curvas de sorção de água. A adição de subprodutos proporcionou cristalinidade ao filme de pectina, atribuída ao seu teor de celulose, e dificilmente alterou a capacidade de retenção de água dos filmes de pectina. No entanto, a pectina contribuiu para apresentar uma umidade de sorção ligeiramente superior no equilíbrio, quando comparada à polpa de goiaba. As temperaturas de transição vítrea encontradas em teores de umidade extremamente baixos, tanto na polpa quanto nos filmes com subprodutos adicionados, indicaram que em teores de umidade intermediários, o conjunto fruta / filme estava no estado borracha em temperatura ambiente, proporcionando maciez ao produto desidratado. As imagens mostraram boa integração dos filmes comestíveis com a superfície dos pedaços de goiaba.
Características físicas e morfológicas de coberturas comestíveis à base de pectina e subprodutos da goiaba aplicados a pedaços de goiaba
Keywords: Psidium guajava L.; differential scanning calorimetry (DSC); X-ray diffraction (XRD); scanning electronic microscopy (SEM); sorption isotherms.; Psidium guajava L.; calorimetria diferencial de varredura (DSC); difração de raios X (XRD); microscopia eletrônica de varredura (SEM); isotermas de sorção.